15 years of Rev Rene - Pagliuca, Lorita Marlena Freitag (Rev Rene, 2015)
Writing an editorial is always a challenge. When drafting a scientific paper one can rely on the literature review, method, results, and discussion with texts supporting or deconstructing what one wants to prove. It has been already said, that No island is an island(1) (Carlo Ginzburg), No man is an island(2) (John Donne) and, therefore, no researcher is an island.